Diurnal variations in algal density and diversity along water column in tropical ponds. - Chua, Nicole Ching Ling. (2013)
Algae are highly diverse species and they are essential in the pond to maintain the aquatic food chain. However, overgrowth of algae will cause fishes to die and results in an unsightly view of the pond. Eutrophication has been recognized as a serious environmental problem causing algae bloom in ponds in Singapore. Furthermore, as Singapore does not have seasonal changes, algae growth becomes more persistent. Ponds in Singapore show scum at different times of the day. Hence, to understand the fluctuations in algal growth, diurnal variations of algae density and diversity were studied weekly for eight weeks with 3 time-points at four different locations of the tropical pond. Algae density and diversity were analyzed microscopically and physical parameters were measured using a multi-parameters instrument. Nutrients were measured using Ion Chromatography and pigments content were measured following extraction protocols. Few external factors such as temperature, conductivity, pH, TDS and nutrients have shown to have effect on algae growth. Diurnally, algae were found to float at the top of water at 7am, then sank to the bottom at 2pm and float back up at 7pm. This showed diurnal variations of algae density and diversity changed in relation to presence of scum.